GREEN TEA CATECHIN LOADED NANODELIVERY SYSTEMS FOR THE TREATMENT OF PANDEMIC DISEASES - SATHEESH BABU NATARAJAN,; SURIYAKALA PERUMAL CHANDRAN,; ANJANEYULU VINUKONDA,; SENTHIL RAJAN D, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Tea (Camellia sinensis, Family: Theaceae) is one of the extremely consumed beverages around the world, behind to water. The brew tea is the merely food product contains abundant quantity of the catechins. Green tea is the least processed and thus contains rich antioxidant, polyphenols, especially catechin called epigallocatechin-3-gallate (EGCG), which is whispered to be responsible for a wide range of the health benefits. The key to the amazing health benefits that are derived from green tea is that the leaves are steamed which preserves the EGCG compound from being oxidized. However, the other varieties of teas are under go fermentation process, which breaks down the potential EGCG and destroy from its healing properties. In reality, green tea has very extensive history dating back thousands and thousands of years ago. However, the pharmacological efficacy and stability of green tea catchiness are primarily depended on the formulation and way to drink to alleviate the deadly diseases with scientific evidence. Nanotechnology is a vibrantly emerging field especially in the pharmaceutical industry to explore a lot of application. The promising nano-delivery system used to enhance the therapeutic efficacy with a minimal dose, minimize the dose-related toxicity, target delivery, site-specific delivery, and controlled/sustain the delivery application. In recent decades, the application of nanotechnology has been utilized for phytopharmaceutical industry including green tea catechins to maximize the health benefits. In this review, we tried our level best retrieve the value of information on nanodelivery application of green tea catchiness for various devastating diseases.